Indian society and culture : for BBA students - Chakraborty,Sreparna (Kalyani Publisher, 2018)
Indian society and culture : for BBA students / Chakraborty,Sreparna. -- Kolkata: Kalyani Publisher, 2018 301 C426 No. of Copies : 1